Stimulating Tourists' Imagination: The Role of Visual Communication in Managing Storynomic Tourism Strategies in the Digital Age - Aliyah, Aliyah; Kartini, Raden Asri; Amanda, Amanda; Sartika, Tik Tik Dewi (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research aims to analyse the role of visual communication in supporting storynomic tourism strategies, particularly how visual elements shape tourist perceptions, emotional connections, and destination attractiveness in the digital age. Materials and methods: A qualitative-descriptive approach was employed, incorporating visual semiotics and representation discourse analysis. Data were collected through digital documentation of social media content, in-depth interviews with tourism content creators and digital travellers, and participatory online observation. Visual materials from Instagram, TikTok, and YouTube accounts (e.g., @wonderfulindonesia) were the primary objects of study. Results: Findings reveal that visuals—through the use of local symbols, colour palettes, illustration styles, and cinematic storytelling—effectively build emotional narratives and trigger the imagination of digital travellers. Content infused with cultural meaning outperformed purely informational visuals in engagement metrics. Social media platforms such as Instagram and TikTok proved particularly powerful in conveying micro-narratives that inspire travel interest. Conclusions: Visual storytelling is a critical component of storynomic tourism, influencing traveller decisions through emotional engagement and digital immersion. A research-based visual communication strategy that prioritises cultural authenticity and emotional resonance is essential for tourism stakeholders aiming to differentiate destinations in the competitive digital landscape.